The TikTok Application: A Virtual Portal for Manifesting the Collective Aspirations of the Masses - Azni, Ulfa Sevia (Talenta Publisher, 2024)
Social media, as a virtual platform for social contact, has undoubtedly brought about significant social changes over time, thanks to the ever-advancing technology of today. As society progresses, the way individuals behave can vary between their actions in the physical world and their actions in the online realm. The omnipresent TikTok application has enthralled a wide array of populations, encompassing both the privileged and the labouring class, across various age brackets. Social change refers to a fundamental shift in the structure and functioning of social relationships, encompassing aspects such as power dynamics, decision-making processes, social influence, family connections, and population patterns. In this instance, the author will examine how the TikTok application might effectively redirect individuals' desires towards an institution or the public in the virtual realm. This research employs a qualitative approach through a literature review, wherein prior studies are analysed and synthesized to create a new body of literature.